STRUCTURAL AND SEMANTIC COMPONENTS OF THE THEMATIC FIELD OF ‘TELEVISION’ IN ENGLISH LINGUOCULTURE - Samatov Farkhod Muminovich (Western European Studies, 2025)
This study explores the structural and semantic composition of the thematic field of "television" within English linguoculture. Employing semantic field theory, conceptual metaphor analysis, and cultural linguistics, the research identifies core and peripheral lexical units associated with television, analyzes their paradigmatic and syntagmatic relations, and uncovers cultural meanings embedded in key terms. By examining both denotative and connotative values of these lexical items, the study provides insight into how television-related language reflects media practices and social norms in Anglophone societies. The findings draw upon theoretical frameworks by Trier, Ufimtseva, Lakoff and Johnson, Crystal, and Sternin.
Keywords: thematic field; semantic field; television